The Effect of Entrepreneurship Education on The Interpersonal Communication Ability of Students of SMA Negeri 1 Parigi - Rismawan, Arip; Sujaya, Krisna; Fauziyah, Azizah (A Social Science and Entrepreneurship Journal, 2023)
This study's goal was to determine the overall impact of entrepreneurship education on the students at SMA Negeri 1 Parigi's interpersonal communication abilities. The issue identified by this study is that students lack interpersonal communication skills, which deters them from starting their own businesses. This research was conducted at SMA Negeri 1 Parigi. This research uses descriptive quantitative and verification methods. The data collection technique in this research is the questionnaire method as the main method using google form and supported by the documentation method. The general description of entrepreneurship education is in the low category with a percentage of 100%, and the general description of interpersonal communication is in the medium and high category, with a medium percentage of 17% and a high category of 83%. This study explains that there is an effect of entrepreneurship education on the interpersonal communication skills of SMA Negeri 1 Parigi students so that Ha is accepted and Ho is rejected. This is explained based on the results of the t test with a calculated t value of 11.17 t table with a value of 1.99006, with a significance value of 0.000 0.05. The results of the coefficient of determination (R2) in this study indicate that the variable of entrepreneurship education in explaining interpersonal communication is 61%.